Literature Review: Patient Services Family-Based Hypertension - Fajar Tri Asih; Endang Triyanto; Lita Heni Kusumawardani (Media Keperawatan Indonesia, 2023)
A healthy family or not using several indicators or markers, in the framework of implementing the Healthy Indonesia Program it has been agreed that there are 12 indicators for family health status markers. With very low coverage, families with family members suffering from hypertension and not being treated regularly are certainly a problem for other family members and the patient himself. The flow of searching for articles uses the PRISMA (Preferred Reporting Items for Literature Reviews and Meta-Analyses) method which begins with collecting articles according to keywords from the various databases used. After that, a check is made for duplicate titles, and the same title is eliminated from the article search process. The search is continued by eliminating articles that have irrelevant titles to the topics to be reviewed. The results of the selection of selected articles were 7 articles. This condition becomes a reference for local governments at both the district and provincial levels to provide appropriate interventions as a solution to these health problems. The goal of achieving this health status is to become a benchmark for the central government to see the success of the health programs that have been implemented so far. public health services as the spearhead of PISPK implementation are required to be able to run the PISPK program thoroughly and cover all areas in the working area of the public health services. Community health center activities through home visits did not end with data collection but continued when carrying out interventions for residents who have health problems. PISPK's further intervention is very important to do in improving the Healthy Family Index. Research results should be disseminated at the Community Health Center to improve public health nursing services.